Development of Android-Based BIPAS Learning Media in MI/SD - Setria Rizal; Silviyanti Silviyanti; Muhammad Syabrina (Genderang Asa: Journal of Primary Education, 2023)
Learning media is something that has an important role in the learning process, with the presence of learning media material that was previously difficult for students to understand or even abstract will become concrete with the help of learning media. The purpose of this study was to produce android-based BIPAS learning media on the theme "Beautiful Togetherness" subtheme "Togetherness in Diversity" Learning 1 which contains Indonesian language, science, and social studies (BIPAS) material. This development research uses the Research and Development (R&D) method with the 4D development model, this model uses 4 stages including Define, Design, Develop and Disseminate. The results of this study produced that the android-based BIPAS learning media is of good quality. Proven by the results of validation by material experts obtained a percentage of 80.68%, while validation by media experts obtained a percentage of 93.33%. so that this product can be said to be valid material experts and media experts. The results of students' responses obtained a percentage of 88.97% in the Very Good category.